Incidence and Lethality of Suicidal Overdoses by Drug Class - Miller, Ted R. (JAMA Netw Open, 2020)
IMPORTANCE: Prior lethality analyses of suicide means have historically treated drug poisoning other than alcohol poisoning as a lumped category. Assessing risk by drug class permits better assessment of prevention opportunities. OBJECTIVE: To investigate the epidemiology of drug poisoning suicides. DESIGN, SETTING, AND PARTICIPANTS: This cross-sectional study analyzed censuses of live emergency department and inpatient discharges for 11 US states from January 1, 2011, to December 31, 2012, as well as Healthcare Cost and Utilization Project national live discharge samples for January 1 to December 31, 2012, and January 1 to December 31, 2016, and corresponding Multiple Cause of Death census data. Censuses or national samples of all medically identified drug poisonings that were deliberately self-inflicted or of undetermined intent were identified using diagnosis and external cause codes. Data were analyzed from June 2019 to January 2020. MAIN OUTCOMES AND MEASURES: Distribution of drug classes involved in suicidal overdoses. Logistic regressions on the state data were used to calculate the odds and relative risk (RR) of death for a suicide act that involved a drug class vs similar acts excluding that class. RESULTS: Among 421 466 drug poisoning suicidal acts resulting in 21 594 deaths, 19.6% to 22.5% of the suicidal drug overdoses involved benzodiazepines, and 15.4% to 17.3% involved opioids (46.2% men, 53.8% women, and <0.01% missing; mean age, 36.4 years). Opioids were most commonly identified in fatal suicide poisonings (33.3%-47.8%). The greatest RR for poisoning suicide completion was opioids (5.20 times the mean for suicide acts that did not involve opioids; 95% CI, 4.86-5.57; sensitivity analysis range, 3.99-6.86), followed by barbiturates (RR, 4.29; 95% CI, 3.35-5.45), antidepressants (RR, 3.22; 95% CI, 2.95-3.52), antidiabetics (RR, 2.57; 95% CI, 1.94-3.41), and alcohol (conservatively, because 30% of death certifiers do not test for alcohol; RR, 2.04; 95% CI, 1.84-2.26). The updated toxin diagnosis coding in International Statistical Classification of Diseases and Related Health Problems, Tenth Revision, used to code the 2016 data revealed that calcium channel blockers also had a high RR of 2.24 (95% CI, 1.89-2.61). Translated to attributable fractions, approximately 81% of suicides involving opioids would not have been fatal absent opioids. Similarly, 34% of alcohol-involved suicide deaths were alcohol attributable. CONCLUSIONS AND RELEVANCE: These findings suggest that preventing access to lethal means for patients at risk for suicide should extend to drugs with high case fatality rates. Blister packing and securely storing lethal drugs seems advisable.